The «Agreement for the Provision of non Consistorial Benefits». An Agreement Half of Way Between the Agreement on Bishops’ Presentation and the Concordat - Martín de Santaolalla Saludes, Pablo (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2018)
The negotiation of the Concordat of August 27, 1953 constituted an arduous work for the Spanish diplomacy. The need to overcome the international isolation in which Franco’s Regime found itself, after Second World War, forced the Department of Foreign Affairs to focus all his efforts both in a big agreement between the Catholic Church and the Spanish Government, and in an explicit and strong support of the United States, then the leading country of capitalist block. Before obtaining this longed Concordat, the Government of Franco and Holy See negotiated several agreements; one of them was the agreement for the provision of non consistorial benefits. This document developed a system to designate all those ecclesiastic charges that were not directly chosen by the Pope by way of a Consistory.